2012
DOI: 10.1149/2.025208jes
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Electrode Voltage and Activation Energy of LiMnxCoyNi1-x-yO2Solid Solutions as Cathode Materials for Li Batteries from First-Principles

Abstract: Layered transition-metal oxides, LiMn x Co y Ni 1-x-y O 2 , have been considered as potential cathode materials for lithium batteries with high energy density. The crystal structures, reversible potentials and activation energies of LiMn x Co y Ni 1−x−y O 2 are studied by means of density functional theory (DFT) calculations within generalized gradient approximation (GGA) and projector-augmented-wave (PAW) method. The larger cell volume with increasing Ni content benefits the capacity of the cathode materials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 66 publications
4
33
0
Order By: Relevance
“…The lattice parameters (a and c) for NaMO 2 crystals of O3 type from present calculations are shown in Table 1, along with previous experimental data and DFT results [19,[44][45][46][47][48][49]. Our calculations are basically in agreement with the experimental results, with a deviation less than 3%.…”
Section: Electrode Potentialssupporting
confidence: 87%
See 2 more Smart Citations
“…The lattice parameters (a and c) for NaMO 2 crystals of O3 type from present calculations are shown in Table 1, along with previous experimental data and DFT results [19,[44][45][46][47][48][49]. Our calculations are basically in agreement with the experimental results, with a deviation less than 3%.…”
Section: Electrode Potentialssupporting
confidence: 87%
“…Calculated AEP is defined as the average value of the nine steps. Experimental AEP within reversible ionic (de)intercalation content are listed and other computational values for LiCoO 2 [49], NaCoO 2 and NaNiO 2 [44] are given in parentheses for comparison when available. DU denotes the drop of U values from low x region (0 6 x 6 1/9) to high x region (8/9 6 x 6 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive studies for the replacement of LCO were conducted by formulating layered oxides with multi-components of the system Li M O 2 ( M = Ni, Mn, and Co); then, the new lamellar compounds LiNi 1-y Mn y O 2 (NMO), LiNi 1−y Co y O 2 (NCO), and LiNi y Mn z Co 1 −y −z O 2 (NMC) were successively proposed [8,9,10,11,12,13]. The performance of LiNi x Mn y Co 1 −x −y O 2 as cathode material relies on the distribution of the transition-metal (TM) cations.…”
Section: Introductionmentioning
confidence: 99%
“…Although the DFT + U correction has shown improved results for redox potential 15 and oxidation energy 16 in transition metal oxides, it was reported that the GGA method is also appropriate for thermodynamic calculations such as formation energy and phase diagram. [17][18][19][20][21] The GGA + U also results in significant errors in the calculated energies of metallic phases of element materials. 20 For clarity, we calculated the total energy difference between E tot (V Ni ) and E tot (bulk) in NCM, which is the main part in the calculation of formation energy (eqn (1)), in each of the GGA and GGA + U schemes, and obtained the difference of 0.38 eV for V ni in NCM, where U-parameters of Ni, Co, and Mn atoms were fitted to the experimental value of open circuit voltage (3.7 V vs. Li + /Li) of NCM.…”
Section: Total Energy Calculationmentioning
confidence: 99%